Post-coronavirus disease 2019 children in Sarajevo-Lessons learnt? (Journal of Health Sciences, 2021)
Introduction: A new disease coronavirus disease 2019 (COVID-19) is with insufficiently known epidemiological characteristics and spectrum of clinical expression in childhood. Children have a lower incidence of this disease with a predominance of mild forms but severe clinical forms, such as among others, acute respiratory distress syndrome, and multisystem inflammatory syndrome may occur, according to current findings. In children with atypical symptomatology and positive or suspicious epidemiological survey, practitioners should consider the possibility of COVID-19.Methods: This study formed the group of 70 children previously healthy or with no pre-existing heart disease from Sarajevo with positive post-COVID history. Following the history of disease and epidemiological data, establishing the 1st day of disease or contact, a detailed cardiovascular examination was performed, including parameters of body weight, height, oxygen saturation, pulse, blood pressure, 12 leads electrocardiogram (ECG) done on Schiller machine, values of polymerase chain reaction (PCR), or serological test on corona: Immunoglobulin (Ig) G and IgM. Echocardiographic examination was done using M, B mode, color, continuous wave, and pulse wave Doppler in standard views. Laboratory blood tests included: Full blood count, creatinine phosphokinase myofibril, creatinine phosphokinase, lactate dehydrogenase; liver enzymes, D dimer, C reactive protein, and urine.Results: Majority of children (64.3%) were asymptomatic. ECG was normal in relation to patients’ age except in eight patients (intermittent palpitations on exertion) who had short PR interval 0.120–0.140 ms, with no delta wave, with heart rate within the normal range according to age, so 24 h ECG Holter was performed without any significant arrhythmias, incomplete right branch block has been documented in 12%, monofocal ventricular ectopic extrasistoly in 15%. Mean IgG, as a marker of infection, showed a statistical significance when compared between age Groups I and II (<5) and older groups: III, IV, and V (>5) (p < 0.05; p = 0.043). PCR test was negative in 9 (70 children), although they showed symptoms, COVID-19 infection clinical data, and positive laboratory findings. Echocardiogram was normal in all patients with normal ejection fraction of the left ventricle.Conclusion: The possibility of COVID-19 in children with atypical symptomatology and positive or suspicious epidemiological survey should be in the focus of every pediatrician at primary care institutions nowadays. Cardiovascular assessment should always be an option in post-COVID patients. Immunological assessment is necessary in post-COVID patients in order to gain a further understanding of PTS status. With more serological testing for severe acute respiratory syndrome coronavirus 2 physicians would be able to make a diagnosis of COVID-19 timely and more accurately, as well as to evaluate the role of asymptomatic children in disease transmission and to assess the importance of protective antibodies and the distribution of COVID-19.